PENINGKATAN MUTU PERGURUAN TINGGI PESANTREN MELALUI ISO 21001 : 2018 - Tohet, Moch; Cahyono, Dimas Eko (Universitas Nurul Jadid, 2020)
Higher education has a vital role in nation-building, it is a means to realize intellectuals in order to organize the life of an established nation. This paper aims to explore efforts to improve the quality of pesantren colleges through ISO 21001: 2018 in producing quality, skilled, and professional generations. The method used in this research is a qualitative approach. The informants in this study consisted of leaders, heads of institutions, and faculty leaders. Data collection techniques are carried out using interviews, observation, and documentation, in order to obtain accurate information about the material being studied. The data analysis technique uses data display, data reduction and drawing conclusions. The results of this study indicate that the application of ISO 21001: 2018 is capable of delivering quality administrative governance to the development and improvement of the quality of pesantren higher education. Do not forget the application of ISO is not the final step and does not automatically become a quality institution, the need for teamwork in increasing self-confidence, communication and developing independence.